2021
DOI: 10.1097/cm9.0000000000001882
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes following transcatheter aortic valve replacement in China: a report from China aortic valve transcatheter replacement registry (CARRY)

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 32 publications
(74 reference statements)
1
22
0
Order By: Relevance
“…TAVR is significantly less common in China than it is in the United States for technical and economic reasons. Despite the fact that no nationwide data on TAVRs has been published in China, the largest multi-center retrospective study [ 19 ], covering seven major sites in China, found that only 1204 patients have had TAVRs between April 2012 and November 2020 in these seven prominent cardiac centers.…”
Section: Discussionmentioning
confidence: 99%
“…TAVR is significantly less common in China than it is in the United States for technical and economic reasons. Despite the fact that no nationwide data on TAVRs has been published in China, the largest multi-center retrospective study [ 19 ], covering seven major sites in China, found that only 1204 patients have had TAVRs between April 2012 and November 2020 in these seven prominent cardiac centers.…”
Section: Discussionmentioning
confidence: 99%
“…Only five studies reported procedural and in-hospital mortality, with a total sample size of 3174 [16,21,22,29,30]. The mean in-hospital mortality rate was 2.28% [16,21,22,29,30]. Among the five studies, Barbash et al [29] (2015) reported the highest in-hospital mortality (3.17%, 42/1327) in Israel.…”
Section: In-hospital Mortalitymentioning
confidence: 99%
“…Eighteen studies reported that a total of 224 out of 13,509 patients died by 30 days after TAVI, giving a weighted mean for 30-day mortality rate of 1.66%, with a weighted standard deviation of 1.2% [8,[17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33].…”
Section: -Day Mortalitymentioning
confidence: 99%
See 2 more Smart Citations